The Effectiveness of Energy Performance Certificates - Evidence from Germany - Hermann Amecke (Climate Policy Initiative, 2011)
Buildings account for about 40% of the final energy consumed in Germany and arguably offer both low-cost and large scale energy efficiency improvement potentials. The Energy Performance Certificate (EPC) was recently introduced to capture this potential by providing information about the energy performance of residential and non-residential buildings to owners and renters. This study evaluates how effective EPCs have been in helping purchasers of dwellings in Germany to incorporate energy efficiency into their home purchasing decisions. The study both assesses to what extent the EPC is an effective information tool and examines explanations for the effectiveness found. The results are based on a survey of 662 resident owners who have purchased a dwelling since 2009. The study aims to inform the discussion around the reimplementation of the EPC's underlying directive, the 2010 Energy Performance of Buildings Directive (EPBD). Member States will implement this directive until 2012.
Keywords: D80; Q40; Q48; 330; Energy Performance Certificates (EPC); energy efficiency; Energy efficient building; Energy saving